2010
DOI: 10.1095/biolreprod.109.077644
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Functional Characterization of a Zebrafish Nuclear Progesterone Receptor1

Abstract: Progestagenic sex steroid hormones play critical roles in reproduction across vertebrates, including teleost fish. To further our understanding of how progesterone modulates testis functions in fish, we set out to clone a progesterone receptor (pgr) cDNA exhibiting nuclear hormone receptor features from zebrafish testis. The open reading frame of pgr consists of 1854 bp, coding for a 617-amino acid-long protein showing the highest similarity with other piscine Pgr proteins. Functional characterization of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
94
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 74 publications
(113 reference statements)
10
94
0
1
Order By: Relevance
“…An in vitro assay carried out using mammalian cell culture has proved that a functional progestin receptor (Pgr) can transactivate target genes in a DHP-dependent manner, supporting the view that DHP is the major native ligand of nuclear Pgr in fish (Chen et al 2010). Using a testicular incubation system, Chen et al (2010) also demonstrated that DHP stimulates the production of 11-KT in a Pgr-dependent manner, while RU486 (a synthetic Pgr antagonist) could inhibit its action by suppressing Pgr-mediated transactivation. Therefore, it has been proposed that Pgr might mediate the actions of DHP in spermatogonial cell proliferation, meiosis initiation, and spermatogenesis in fish.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…An in vitro assay carried out using mammalian cell culture has proved that a functional progestin receptor (Pgr) can transactivate target genes in a DHP-dependent manner, supporting the view that DHP is the major native ligand of nuclear Pgr in fish (Chen et al 2010). Using a testicular incubation system, Chen et al (2010) also demonstrated that DHP stimulates the production of 11-KT in a Pgr-dependent manner, while RU486 (a synthetic Pgr antagonist) could inhibit its action by suppressing Pgr-mediated transactivation. Therefore, it has been proposed that Pgr might mediate the actions of DHP in spermatogonial cell proliferation, meiosis initiation, and spermatogenesis in fish.…”
Section: Introductionmentioning
confidence: 85%
“…However, it has been shown that DHP is produced by both mature and immature testes at different stages, indicating its diverse roles before and during spermatogenesis in rainbow trout (Oncorhynchus mykiss; Depeche & Sire 1982). Recent reports have revealed that DHP might play critical roles in the initiation of meiosis in Japanese eel (Anguilla japonica) and in the early stages of spermatogenesis in Atlantic salmon (Salmon salar), cod (Gadus morhua), and zebrafish (Danio rerio) (Chen et al 2010(Chen et al , 2011(Chen et al , 2012(Chen et al , 2013. Furthermore, it has been proven in in vitro experiments that DHP can induce the conversion of 11b-hydroxytestosterone to 11-ketotestosterone (11-KT, the main androgen in fish) by stimulating the activity of 11b-hydroxysteroid dehydrogenase (encoded by cyp11b2) in Japanese eel and zebrafish , Chen et al 2010.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations